Impacts of the Internet on Health Inequality and Healthcare Access: A Cross-Country Study - Yu, Jiajie; Meng, Shuang (Frontiers in Public Health, 2022)
Access to information and resources through the Internet has become an increasingly critical aspect of contemporary life. Based on the WHO Health Equity Assessment Toolkit (HEAT) and cross-country panel data, this paper investigates the effect of Internet access on health inequality across different income groups. The results indicate that access to the Internet significantly improves the average health condition and alleviates health inequality. In addition, employing cross-country data from the Global Burden of Disease (GBD) database, this paper further examines the social and economic determinants of access to healthcare. Specifically, it is found that Internet access significantly facilitates healthcare access and mitigates the negative impact of income inequality on healthcare access. Considered together, these findings shed light on the importance of the Internet in reducing health inequality and improving healthcare access.